Penerapan Ekstrakurikuler Al-Qur’an dengan Metode Talaqqi dalam Meningkatkan Kemampuan Membaca Al-Qur’an Siswa MI Thoriqotul Hasan - Rifai, Muhammad Amin; Yaqin, Firdaus Ainul; Purwantoro, Farich (Jurnal Pendidikan Madrasah, 2026)
This study aims to analyze the implementation of the talaqqi method in Qur’anic extracurricular activities and to examine its effectiveness in improving students’ reading fluency. The research was conducted at MI Thoriqotul Hasan, involving the principal, supervising teacher, and students as research subjects. A descriptive qualitative approach was employed, with data collected through observation, interviews, and documentation. The findings indicate that the implementation of the talaqqi method is carried out systematically through planning, implementation, and evaluation stages. The method has a positive impact on students’ Qur’anic reading ability, as evidenced by improvements in reading fluency, accuracy of makhraj (articulation of letters), and understanding as well as application of tajwid rules. Additionally, students demonstrate increased confidence and learning motivation. Through direct interaction between teacher and students and immediate corrective feedback, the talaqqi method proves to be effective in enhancing the quality of Qur’anic learning. Despite challenges such as varying initial student abilities and limited instructional time, the method remains relevant and feasible to be further developed as a learning strategy in Islamic educational extracurricular programs.